The semiotics of social justice: a multimodal approach to examining social justice issues in videogames. Issue 5 (2nd September 2020) - Hawreliak, Jason; Lemieux, Amélie
ABSTRACT: This article explores how principles of multimodality can be effectively incorporated into game analysis in the context of social justice. The authors use a multimodal framework to assist developers, researchers, and educators in better understanding representations of class, race, and gender in videogames. Videogames are multimodal in nature: not only do they 'remediate' and adopt the representational practices of other media, but also employ algorithmic, procedural, haptic, and interactive forms of expression. Videogames are uniquely situated to represent systemic oppression and privilege through what Ian Bogost calls 'procedural rhetoric, ' i.e. the representation of systems through computational media. Videogames' high multimodality allows players to experience and interact with systems of oppression and privilege in ways that other media cannot. To define these concepts, the paper will include examples from several videogames deal with issues of representation either implicitly or explicitly, including CartLife, a retail simulator; Overwatch, a competitive First-Person Shooter; and Apex: Legends, a battle-royale First-Person Shooter.